2021
DOI: 10.3390/ijms22031472
|View full text |Cite
|
Sign up to set email alerts
|

Role, Laboratory Assessment and Clinical Relevance of Fibrin, Factor XIII and Endogenous Fibrinolysis in Arterial and Venous Thrombosis

Abstract: Diseases such as myocardial infarction, ischaemic stroke, peripheral vascular disease and venous thromboembolism are major contributors to morbidity and mortality. Procoagulant, anticoagulant and fibrinolytic pathways are finely regulated in healthy individuals and dysregulated procoagulant, anticoagulant and fibrinolytic pathways lead to arterial and venous thrombosis. In this review article, we discuss the (patho)physiological role and laboratory assessment of fibrin, factor XIII and endogenous fibrinolysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 164 publications
0
16
0
Order By: Relevance
“…Furthermore, FXIII is an important determinant of fibrin clot structure and susceptibility to lysis. It promotes fibrin clot compaction and elasticity, facilitates binding of antifibrinolytic proteins within the clot and may promote erythrocyte retention in the clot which also renders the clot less permeable [5]. Finally, the clot is stabilized after incorporation of alfa2-plasmin inhibitor [6].…”
Section: Clot Formation and Fibrinolysismentioning
confidence: 99%
“…Furthermore, FXIII is an important determinant of fibrin clot structure and susceptibility to lysis. It promotes fibrin clot compaction and elasticity, facilitates binding of antifibrinolytic proteins within the clot and may promote erythrocyte retention in the clot which also renders the clot less permeable [5]. Finally, the clot is stabilized after incorporation of alfa2-plasmin inhibitor [6].…”
Section: Clot Formation and Fibrinolysismentioning
confidence: 99%
“…These patients, especially those with critical limb threatening ischemia, present decreases in natural anticoagulants (proteins C and S) and coagulation factors FIX, FXI, and FXII [3]. Thus, dysregulated procoagulant, anticoagulant, and fibrinolytic pathways lead to arterial and venous thrombosis in patients with PAD [4]. The contribution of atherosclerosis, and ultimately of thrombosis, to ischemic risk in PAD has formed the basis for treatment with antithrombotic therapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke patients have thicker fibers compared to healthy donors. Patients within the acute phase of ischemic stroke demonstrated reduced clot permeability and decreased fibrinolysis, contributing to the thrombosis mechanism (93,137,138). Rooth et al (114) showed that the changes observed during the acute phase of ischemic stroke persist for more than 60 days after the stroke event.…”
Section: Pathology and Clinical Prognosismentioning
confidence: 99%
“…Rooth et al (114) showed that the changes observed during the acute phase of ischemic stroke persist for more than 60 days after the stroke event. Patients with acute ischemic stroke associated with carotid artery disease (CAD) exhibited slower clot lysis compared to controls without CAD history (93). Fibrin clot density is correlated with neurological deficit upon both admission and discharge of acute ischemic stroke patients (137).…”
Section: Pathology and Clinical Prognosismentioning
confidence: 99%
See 1 more Smart Citation